DINAMIKA ASEAN DALAM MENYELESAIKAN KRISIS POLITIK PASCA-KUDETA MILITER MYANMAR 2021 - Argaditya, Raynor (2023)
This study discusses ASEAN dynamics to settle the political crisis that occurred in Myanmar after the 2021 military coup. In addition, this study uses qualitative method by focusing on data in the field. Regionalism theory is used to study regional organizational policies. The coup concept examines the impact of the coup so as to move ASEAN to be actively involved. The research method used is a qualitative method by John W. Creswell using primary and secondary data sources. Researchers used two data analysis techniques, namely descriptive analysis and interview analysis. In this study, it was concluded that ASEAN failed due to the adhered to non-interference principle became an obstacle to ASEAN's responsibility towards Myanmar and it was necessary to prioritize other principles, namely the rule of law, good governance, democratic principles, and constitutional government. In addition, ASEAN remains committed to supporting Myanmar in its efforts to return to normal conditions in accordance with the wishes of the people of Myanmar, bearing in mind that one of the points contained in the Five-Point Consensus (5PC) is calling for constructive dialogue between all parties in order to achieve a peaceful solution.